Rebel-to-political and back? Hamas as a security provider in Gaza between rebellion, politics and governance. Issue 6 (18th September 2016) - Berti, Benedetta; Gutiérrez, Beatriz
ABSTRACT: After winning the 2006 Palestinian Legislative Council (PLC) elections and subsequently taking control of the Gaza Strip in the summer of 2007, the Palestinian Hamas – a hybrid political, social and military actor – undertook a complex process to ascertain authority and control over Gaza. The article focuses on understanding Hamas's performance as a political party and a "rebel government" as well as the impact of this newly acquired role on the group's strategy. Relying on primary sources, field-work and interviews with members of the Hamas government and its security sector, the study looks at Hamas's role as a security provider and analyses the complex relationship between the institutionalized security sector and the group's insurgent armed wing. Examining Hamas's logic as a security provider and exploring the inherent tensions between political and insurgent logics allows for a better understanding of both the rebel group's role as a political actor and the broader challenges behind the successful rebel-to-political transformations of non-state armed organizations. In doing so it contributes to the emerging literature on non-state actors' shifts between ballots and bullets and on their potential role as alternative governance providers.